English: Infeksi Jamur Pascapanen pada Biji Kopi Arabika (Coffea arabica Linnaeus) di Daerah Sentra Kopi Arabika, Provinsi Sumatera Barat, Indonesia - Martinius, Martinius; Fauzi, Aziz; Resti, Zurai (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2022)
Post-harvest fungi attacks in storage can reduce the quality of Arabica coffee. The study aimed to determine the level of infection and types of post-harvest fungi in Arabica coffee beans and their quality. The research was carried out at the Phytopathology Laboratory of Plant Pests and Diseases Department and the Seed Technology Laboratory of Agronomy Department, Agriculture Faculty, Universitas Andalas, Padang, from June to August 2021. The infection level of post-harvest fungi was detected using the blotter method. Physical quality was determined based on the percentage of defects, and the quality of the coffee beans was classified according to the Indonesian National Standard (SNI). The samples were taken from three collectors in each of the three central districts of Arabica coffee, West Sumatera province (Solok Selatan, Pesisir Selatan, Lima Puluh Kota) and one sample from Solok Radjo Cooperative as a comparison. The results showed that post-harvest fungi that attacked Arabica coffee beans in West Sumatra belong to the Aspergillus genus, namely Aspergillus niger, A. flavus, and A. ochraceus. The highest post-harvest fungi attack was from Lima Puluh Kota (63.67%), and the lowest was from Solok Radjo (27%). The fungus with the highest infection rate was A. niger (38.83%), and the lowest was A. flavus (0.53%). The best quality of Arabica coffee beans was found in Solok Radjo (quality 3), with a water content that suitable with SNI standards.